ANALISIS TRANSFORMASI BANK DIGITAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setiyo Purwanto; Didin Hikmah Perkasa (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
Digital bank transformation is the effect of the rapid development of digital technology that has entered all sectors of life. The investor community sees the development of digital bank transformation into an exciting new alternative in the future. This study aims to analyze the effectiveness of the performance of digital banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period based on stock prices (HS) which are influenced  by return on assets (ROA), return on  equity (ROE), debt to equity ratio  (DER) mediated by capital adequacy ratio (CAR).  This type of research is quantitative research using secondary data based  on financial statements published on the IDX. The data processing testing technique in this study uses the smartPLS statistical program test tool. In the results of this study, it was found that ROE directly affects stock prices, as well as high CAR positions can increase the influence of digital bank stock prices. This can be a practical reference for investors who are interested in digital bank stocks that have been listed on the IDX. In addition, the growth of digital banks can be a threat to the existence of conventional banks in Indonesia